BEHAVIORAL TRANSFORMATION: SHAPING ENVIRONMENTALLY CONSCIOUS STUDENT CHARACTERS THROUGH PLASTIC WASTE PROCESSING IN ELEMENTARY SCHOOLS - Amelia, Risky Nuri; Pasongli, Hernita; Marthinu, Eva; Aryuni, Vrita Tri; Safitri, Yuni Andriyani; Nasution, Lely Adriani; Ummah, Kuntum Chairum (-, 2025)
This community service aims to instill awareness of the importance of protecting the environment in grade 5 students of SD Islamiyah 1 Ternate City through plastic waste recycling activities. This activity involves providing material on waste management, waste sorting practices, and making accessories from plastic waste. The results showed a significant increase in students' knowledge about waste and their skills in recycling. Students enthusiastically participated in the activities and succeeded in creating valuable products from waste that was previously considered useless. This not only increases students' knowledge and skills, but also fosters an attitude of caring for the environment. This activity is in line with the independent learning curriculum which emphasizes character development and student independence. By integrating waste management into the curriculum, schools can create a learning environment that supports environmentally friendly living habits. As with the goals of the SDGs, namely quality education, responsible consumption and production, and action against climate change. Overall, this study succeeded in instilling a spirit of love for the environment in students from an early age. This activity is not only beneficial for students, but also contributes to environmental conservation efforts. Through this activity, it is hoped that students can become agents of change and invite the surrounding environment to participate in preserving the environment.